"Rusticall chymistry": Alchemy, saltpeter projects, and experimental fertilizers in seventeenth-century English agriculture. (December 2022) - Niermeier-Dohoney, Justin
As the primary ingredient in gunpowder, saltpeter was an extraordinarily important commodity in the early modern world. Historians of science and technology have long studied its military applications but have rarely focused on its uses outside of warfare. Due to its potential effectiveness as a fertilizer, saltpeter was also an integral component of experimental agricultural reform movements in the early modern period and particularly in seventeenth-century England. This became possible for several reasons: the creation of a thriving domestic saltpeter production industry in the second half of the sixteenth century; the development of vitalist alchemical theories that sought a unified explanation for the "growth" of minerals, metals, and plants; the rise of experimental natural philosophy; and the mid-seventeenth-century dominance of the English East India Company in the saltpeter trade, which allowed agricultural reformers to repurpose domestically produced saltpeter in agriculturally productive ways. This paper argues that the Hartlib Circle – a loose network of natural philosophers and social reformers – adopted vitalist matter theories and the practical, experimental techniques of alchemists to transform agriculture into a more productive enterprise. Though their grandiose plans never came to fruition, their experimental trials to develop artificial fertilizers played an early role in the origins and development of saline chemistry, agronomy, and the British Agricultural Revolution.